MBKM Membangun Desa : Meningatkan Perkembangan UMKM dengan Literasi Digital di Desa Neglasari - Ida Jalilah; Herdiana Nugraha; Sifa Nur Azizah; Putri Latifha; Elsa Sulistiani (Digital Bisnis: Jurnal Publikasi Ilmu Manajemen dan E-Commerce, 2025)
This research aims to implement the Merdeka Belajar Kampus Merdeka (MBKM) membangun desa program through improving digital literacy in Neglasari Village, Majalaya District, Bandung Regency. The program focuses on assisting MSMEs in utilizing digital platforms for product marketing and education on stunting prevention. The implementation method includes community needs surveys, training module development, and field coordination. The results showed an increase in knowledge and skills of MSME actors in creating digital promotion content and public awareness about stunting. This program is expected to increase MSME income and the quality of life of the village community.